Cognitive concept learning via granular computing for big data - Li, Jinhai; Huang, Chenchen; Xu, Weihua; Qian, Yuhua; Liu, Wenqi (2015 International Conference on Machine Learning and Cybernetics (ICMLC), 2015)
In this paper, analysis of time complexities of existing granular-computing-based cognitive concept learning method-s is provided by numerical experiments. Moreover, technical problems are addressed when the existing cognitive concept learning methods are applied to big data.